PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, KECERDASAN SPIRITUAL, DAN KECERDASAN ADVERSITY TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (STUDI KASUS PADA MAHASISWA AKUNTANSI DI SURAKARTA) - Ismi Nur Halimah; Rina Trisnawati Trisnawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of emotional intelligence, intellectual intelligence, spiritual intelligence, and adversity intelligence on the level of accounting understanding. The type of data used is quantitative. Data was collected using a questionnaire. The samples studied were accounting students at the University of Muhammadiyah Surakarta, Sebelas Maret University, and Slamet Riyadi University with 100 respondents. Data analysis using SPSS version 25.0 program. The statistical method used to test the hypothesis is multiple linear regression analysis. The result show that emotional intelligence and adversity intelligence had an effect (significantly), while intellectual intelligence and spiritual intelligence had no effect (not significant) on the level of accounting understanding.